Makna Denotasi dan Konotasi Dalam Novel 127 Days Karya Nadzira Shafa - Sinta; Desty Endrawati Subroto; Mahpudoh (Mataram University, 2026)
This research is motivated by the importance of understanding denotative and connotative meanings in literary works, particularly novels, to understand the messages conveyed directly and implicitly. This study aims to describe the denotative and connotative meanings in the novel